2020
DOI: 10.3390/toxics8040097
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-Functional Alterations in the Gills of a Seawater Teleost, the Ornate Wrasse (Thalassoma pavo L.), after Short-Term Exposure to Chlorpyrifos

Abstract: Chlorpyrifos (CPF) is an organophosphorus insecticide commonly used for domestic and agricultural purposes. The risk posed by environmental contamination from CPF is well acknowledged, and it has been detected worldwide in aquatic habitats and coastal areas. In addition, due to its slower degradation in seawater compared to freshwater, CPF is of particular concern for marine environments. Here, we investigated for the first time the morpho-functional alterations induced by CPF on the gills of Thalassoma pavo, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…Padmini et al (2021) reported in the fish Channa gachuva due to the present studied toxicant Dichlorvos in sublethal concentration for 30 days, Juan et al (2021) in the fish Solea senegalentis due to Malathion too had an impact of the gill architectural damage. Rachale et al (2020) in the sea water fish, Thallassoma pavu to 96h exposure only (a short term) of chlorpyrifos as toxicant, scattering of globlet cells apart from the severe damage of the tissue as in the present study reported which impair the respiration, the important physiological process. Kadam and Patl (2019) in the fish Channa gachua due to exposure of Dichlorvos in lethal concentration (Duration of the experiment was 96h only) and similar changes as alterations were reported as in the present study.…”
Section: Gillsupporting
confidence: 55%
“…Padmini et al (2021) reported in the fish Channa gachuva due to the present studied toxicant Dichlorvos in sublethal concentration for 30 days, Juan et al (2021) in the fish Solea senegalentis due to Malathion too had an impact of the gill architectural damage. Rachale et al (2020) in the sea water fish, Thallassoma pavu to 96h exposure only (a short term) of chlorpyrifos as toxicant, scattering of globlet cells apart from the severe damage of the tissue as in the present study reported which impair the respiration, the important physiological process. Kadam and Patl (2019) in the fish Channa gachua due to exposure of Dichlorvos in lethal concentration (Duration of the experiment was 96h only) and similar changes as alterations were reported as in the present study.…”
Section: Gillsupporting
confidence: 55%
“…The edema formation in embryos reported in the larvae exposed to CPF could be explained by osmoregulation failure associated with gill damage. Indeed, many studies have substantiated the highly toxic effect of CPF on gill cells across various species [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%